CORRUPTION FORMATION, FACTORS AND IMPACT ON SOCIETY (TAMADDUN NURI JURNALI, 2025)
Corruption undermines not only the legal system, but also democratic processes and social justice, which ultimately reduces trust and stability in society. People are often forced to do things against the law to get out of economic difficulties. Economic inequality also exacerbates this process. The presence of corruption in society and its acceptance as normal, as well as the weakening of moral standards, are also important factors. If corruption is taken lightly by society or if systematic measures are not taken to prevent it, it can become more widespread and persistent. The causes of corruption depend on various factors, and problems in the economic, political, social and legal systems contribute to its widespread spread. The lack of an effectively functioning judicial system, law enforcement and social control systems in the country are one of the main reasons for the commission of corruption.